The tinder box - Carey, M. R., 1959- (Orbit, 2026)
In a kingdom forgotten by history, a legend unfolds ... Wounded in his county's endless wars, former soldier Mag Tresti finds work in the home of a reclusive widow, Jannae Mirchella. But Jannae is more than she seems. A witch of great skill and might, she hides her powers and her deep-laid plans behind a mask of harmless respectability. When a dead demon falls out of the sky, the fates of the soldier and the witch are irrevocably intertwined. On the demon's body Mag finds a tinderbox - an artefact of terrifying magical power that can not only grant his every wish, but also change the fate of nations. This is a tale of spellcraft and devilry, of witchcraft and trickery - of the wickedness that resides within a few, the goodness that lies deep within us all, and the choices on which our lives turn.